[(μ2-H)(η2-Ge4)ZnPh2]3−, an edge-on protonated E4 cluster establishing the first three-center two-electron Ge–H–Ge bond. Issue 87 (17th October 2018) - Henneberger, Thomas; Klein, Wilhelm; Dums, Jasmin V.; Fässler, Thomas F.
Abstract : The first example of a protonated and a rare example of a metal complex of the tetrahedral tetrel cluster anion [Ge4 ] 4− was obtained from a solution of K6 Rb6 Ge17 in liquid ammonia in the presence of ZnPh2 and [18]crown-6. Abstract : The first example of a protonated and a rare example of a metal complex of the tetrahedral tetrel cluster anion [Ge4 ] 4− was obtained from a solution of K6 Rb6 Ge17 in liquid ammonia in the presence of ZnPh2 and [18]crown-6. In [K([18]crown-6)][Rb([18]crown-6)]2 [HGe4 ZnPh2 ]·8NH3 (1 ) one ZnPh2 molecule and one H atom are bound to opposite, significantly elongated edges of a distorted Ge4 tetrahedron. DFT calculations confirm the experimentally found interatomic distances and reveal a structural proof of a three-center two-electron Ge–H–Ge bond.